A literature review of content elements in supervision training courses (UCL Press, 2023)
The main aim of this article is to explore, through a literature review, how five content elements identified in previous research (assessment, communication, ethics, feedback, and learning and supervision theories) are constituted in practical supervision settings and in educational supervision training for post-degree professionals. A further aim is to identify fields of tension in supervision when incorporating the elements in supervision. To address these aims, a literature review was undertaken with a focus on the content elements. The results show that the explored content elements have the potential to not only enhance supervision, but also point to the existence of generic supervision competences, which are valid for several professions. The results also present four fields of tension in supervision settings; these fields of tension imply challenges, such as the tension between theory and practice, and the tension between the supervisee's autonomy and dependency. Based on the results, the article discusses practical implications for supervision training courses.